Filósofos en 90 minutos. - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (90 minutos., 2017)
The Pack Filósofos 3 collection brings together 6 of the most outstanding philosophers of the Modern Age.